How does body mass index impact self-perceived health? A pan-European analysis of the European Health Interview Survey Wave 2. Issue 2 (12th October 2022) - Narciso, Joana; Croome, Natasha
Abstract : Background: Obesity remains a major global public health issue, despite numerous attempts to address it. Health behaviour theories suggest that a misconception of how excess weight affects general health may be preventing individuals from taking action towards addressing it. The present study explores this relationship in European countries. Methods: This study analysed cross-sectional secondary data collected as part of the European Health Interview Survey Wave 2 (2013–2015), with a total sample of 299 846 participants. The association between body mass index and self-perceived health was analysed using logistic regression models. Age, sex, country, degree of urbanisation and level of education were included in the model to determine excess weight's independent contribution to self-perceived health over and above these variables. Results: The majority of the sample was in the excess weight category (52.92%; n=155 812), with only Austria and Luxembourg reporting a higher proportion of normal weight than excess weight. An analysis of self-perceived health revealed that most individuals perceived themselves to be in good health (42.88%; n=128 579). Logistic regression results show that overweight individuals were more likely to report being in poorer self-perceived health (OR=1.27, 95% CI 1.25 to 1.29) compared with normal weight individuals. The same effect was observed for individuals in the obese class I (OR=2.00, 95% CI 1.96 to 2.05), obese class II (OR=3.00, 95% CI 2.88 to 3.13) and obese class III (OR=4.38, 95% CI 4.07 to 4.71) categories. However, this study did not find a rigid pattern of association between excess weight and self-perceived health across European countries. Conclusion: In general, a higher body mass index category is associated with poorer self-perceived health, suggesting that the majority of the study population have a correct perception of how their weight affects their health. However, in some key countries this relationship is not observed and should be further explored.